E-Gold and Investment Challenges: How Digital Gold Works for Economic Recovery after Covid-19 Pandemic - Soi, Andi Bahri; Yusuf, Hardyansyah; Damirah, Damirah (Institut Agama Islam Negeri (IAIN) Curup, 2023)
Purpose: This study aims to analyze the urgency of gold (e-gold or digital gold) invested for economic recovery after Covid-19 pandemic.Design/Method/Approach: This study applied descriptive qualitative with a literature review approach. The data collected through documentation from authoritative agent on investment business and observation on economic turbulence during the days of Covid-19 pandemic. The data obtained from market review reports, finance symposium summary, economic and business news, article journals, and some relevant books. While the data analysis technique developed base on conclusion drawing technique in order to fine out a systematical analysis as well as objective conclusion.Findings: The results show that gold investment is really recommended because more profitable and gold performed relatively better than many other assets in the early pandemic stages. Besides, the digital transaction was appointed in the Qurâ€™an, Hadith and `Ijmaâ€™. Meanwhile, there are two opinions regarding allowance and prohibition related to digital gold investment. First, it is forbidden due to the payment by credit not cash. In addition to the four madzhabs' opinion, this transaction must be complied the cash transaction requirements in order to prevent the usury. The second is Ibn Taimiyah's opinion and DSN-MUI regulation shown that as long as the transaction fulfills the requirement, it is allowed.Originality/Values: The main contribution of this study concern on filling the gap of how urgency the e-gold investment for recovering the economic impact of pandemic and how e-gold investment according to the Islamic economic perspective.Â